2018
DOI: 10.1111/1744-1633.12300
|View full text |Cite
|
Sign up to set email alerts
|

Home hospitalization for the surgical and conservative treatment of acute calculous cholecystitis

Abstract: Aim: Acute calculous cholecystitis is a frequent complication of gallstones that can manifest in up to 10-15 per cent of previously asymptomatic patients. Current guidelines recommend laparoscopic cholecystectomy as the gold standard treatment; however, the presence of surgery risk factors might compel physicians to opt for conservative treatment, which is often associated with longer hospital stay. Home hospitalization could be an alternative to inpatient stay for these patients. Patients and Methods: The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Although laparoscopic cholecystectomy is the technique of choice for acute cholecystitis (AC), including in elderly patients, [1][2][3][4] it is not always performed during the AC episode. A Cochrane review 5 found no significant differences between early and late laparoscopic cholecystectomy, but did find trials indicating that early laparoscopic cholecystectomy during AC seems safe and may shorten the total hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…Although laparoscopic cholecystectomy is the technique of choice for acute cholecystitis (AC), including in elderly patients, [1][2][3][4] it is not always performed during the AC episode. A Cochrane review 5 found no significant differences between early and late laparoscopic cholecystectomy, but did find trials indicating that early laparoscopic cholecystectomy during AC seems safe and may shorten the total hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…The 69 studies included 38 (55.1%) randomised trials [ 30 – 42 , 44 , 45 , 48 – 50 , 54 – 56 , 62 – 67 , 72 , 73 , 77 83 , 92 94 , 97 , 99 , 102 – 110 , 115 – 122 , 125 127 , 130 139 ] and 31 (44.9%) non-randomised studies [ 43 , 46 , 47 , 51 53 , 57 – 61 , 68 – 71 , 74 76 , 84 – 91 , 95 , 96 , 98 , 100 , 101 , 111 – 114 , 123 , 124 , 128 , 129 ] (Table 2 and Additional file 1 : Table S2). The included RCTs were largely judged as overall low (1/38; 2.6%) and unclear risk of bias (25/38; 65.8%; Table 2 and Additional file 1 : Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Four RCTs and seven non-randomised studies reported this outcome [ 31 33 , 36 38 , 52 , 53 , 60 , 68 , 74 , 81 84 , 87 – 91 , 101 ]. We performed no synthesis for this outcome as the outcomes used were defined inconsistently, and outcome data were incomplete in four studies.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with severe AC were treated on an individual basis, with admission to the intensive care unit when they met the criteria. In selected cases, patients with mild AC were attended to at home by the home hospitalization services 23 .…”
Section: Management In the Emergency Departmentmentioning
confidence: 99%